PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP LOYALITAS MELALUI KEPUASAN WISATAWAN NUSANTARA PADA MASKAPAI LION AIR DI BALI - Hamonangan Sinaga, Christian; Sudiarta, I Nyoman; Sasrawan Mananda, I GPB. (Jurnal IPTA (Industri Perjalanan Wisata), 2016)
This research has purposed to find out the influence of price, service quality, loyalty and mediates satisfaction in correlation to price and loyalty to domestic tourist satisfaction at Lion Air Company Bali. The research used thepurposive sampling approach to 70 respondents of the Lion Air in Bali. Location of this research is at Domestic departure terminal of Ngurah Rai International Airport Tuban – Bali. The research was using two variables, those are the independent variable (X), and the dependent variable (Y). The analysis method used are the validity and instrument reliability test, normality test, and path analysis test. Based on result analysis, indicators in this research are valid and reliable. There is a positive and significant influence between the price to satisfaction of local tourists at Lion Air airline in Bali, there is positive and significant influence between service quality to satisfaction of local tourists at Lion Air company in Bali. There is positive and significant influence between satisfaction to the loyalty of local tourists at Lion Air airline in Bali. There is positive and significant influence between the price to the loyalty of local tourists at Lion Air airline in Bali. There is positive and significant influence between service quality to the loyalty of local tourists at Lion Air airline in Bali. Therefore future research is necessary to conduct further research using other variables suspected to affect the loyalty rating.
Keywords: Price, Service Quality, Loyalty, Satisfaction